Determination of wearproofness of contact wire by the method of complete factor experiment - Скуріхін, Владислав Ігорович (Technology audit and production reserves, 2014)
Using complete factor experiment, the analysis of the possibility of using steel-aluminum contact wire of the new sample during operation in the city contact network was conducted in the paper. The main objective of the study is to conduct this analysis, taking into account the following factors: the pressing force of the current collector to the contact wire, the road grade, the load current on the contact wire. During the performance tests, it is sometimes impossible to directly assess the impact of this or that method, implemented in the contact "contact wire - current collector" (the change in specifications, etc.) on the wire wear, and efficiency has to be judged only by the change in overhaul life of runners, suggesting that the inserts wear-rate reduction is accompanied by the wire wear-rate reduction. This assumption is correct in some cases, but this approach is not entirely correct but in others. The presented mathematical model allows to state that the load current has the most destructive influence on the contact wire since it has the largest ratio of the absolute value. The proposed steel-aluminum contact wire is more appropriate to use at low-traffic sites, slopes, depot sites and zero-run sites since the contact wire wear is minimal at these sites. The research results can be applied by design engineers in designing transport contact network.